Florence Lydia Graham, 2020: Turkisms in South Slavonic Literature: Turkish Loanwords in Seventeenth- and Eighteenth-Century Bosnian and Bulgarian Franciscan Sources: Oxford: OUP. 409 pp. - Johnson, A. Jakob (Slavia Centralis, 2021)
The author presents the work of F. Lydia Graham: Turkisms in South Slavonic Literature: Turkish Loanwords in Seventeenth- and Eighteenth-Century Bosnian and Bulgarian Franciscan Sources (2020).